On the use of optically trapped dust particles as micro-probes in process plasmas - Schneider, V.; Kersten, H. (Вопросы атомной науки и техники, 2013)
In this paper we outline the progress in the development of an optical system for particle manipulation as a plasma diagnostics method. We demonstrate basic principles and preliminary experimental results for optical trapping of microparticles in a plasma. A counter-propagating laser beam was used to trap particles in water as well as in an RF discharge. The experiments indicate that it is possible to manipulate particles, which are levitating in the plasma sheath, to obtain information on the sheath and plasma parameters.